WILMO: an automated profiling system for coastal waters - Deschner, Stephan C.; Bojens, Gero; Orhan, Kadir; Nasukha, Afifah; Voigt, Wolfgang (Frontiers in Marine Science, 2024)
Stationary in situ measurements conducted in close proximity to the shoreline present unique challenges. The shallow depth, automated profiling and accessibility for maintenance, particularly in the context of biofouling, are key considerations. The WInch for Long-term MOnitoring (WILMO), a solution designed to meet these requirements, is therefore presented. The fully automated system keeps the sensitive devices outside of the water until a profiling cycle is initiated, reducing the available settling time for species on the surface of the sensors. The design leverages common hardware and is structured in distinct units. This feature facilitates the interchangeability of individual hardware components and the implementation of a unifying software system capable of simultaneously managing all elements of WILMO. Using wireless broadband communications, WILMO can be fully controlled remotely, allowing for adjustments to the setup and monitoring of system functionality through a special web interface. The data are transmitted to a server with adjustable frequency and a post processing tool prepares them for analysis. The system underwent rigorous testing and demonstrated effective performance in northern Bali, Indonesia, between March and December 2022, gathering physical and biogeochemical time series data. The consistency of the data is validated through comparison with other instruments to ensure data quality. The results obtained are employed to ascertain the suitability of the special flow velocity sensor in this context. WILMO is a demonstrably reliable device, easily manageable and perfectly suited for long-term coastal monitoring.